2001
DOI: 10.1515/jbcpp.2001.12.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Heart Rate Variability Following Acclimation to Heat

Abstract: We studied the sympatho-vagal balance during acclimation to heat in eight healthy individuals. The subjects, dressed in shorts and tennis shoes, underwent a 10 d procedure of acclimation. Daily exposure lasted 115 min--5 min rest followed by 2 bouts of 50 min exercise (walking on a treadmill at a work load of approximately 350 watt) separated by 10 min rest-at 40 degrees C and 40% relative humidity. We analyzed the time and frequency domains of 256 R-R intervals, toward the end of the second bout of exercise, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Our results partly support this notion demonstrating that 60 % of the heat acclimation-induced bradycardia was lost within 2 weeks. nevertheless, while some authors proposed that this heat acclimation-induced heart rate reduction is caused by increased parasympathetic activity (Horowitz and Meiri 1993;Epstein et al 2010), others reported an increase in sympathetic tone following heat acclimation (Frank et al 2001), or alterations between sympathetic and parasympathetic dominance at different phases of heat acclimation (Horowitz and Meiri 1993). Our study clearly demonstrated that heat acclimation was accompanied by vagal dominance, which was observed as early as the rest period of the heat tolerance test conducted during day 14 and remained apparent until the end of the test for the majority of the HrV indices extracted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results partly support this notion demonstrating that 60 % of the heat acclimation-induced bradycardia was lost within 2 weeks. nevertheless, while some authors proposed that this heat acclimation-induced heart rate reduction is caused by increased parasympathetic activity (Horowitz and Meiri 1993;Epstein et al 2010), others reported an increase in sympathetic tone following heat acclimation (Frank et al 2001), or alterations between sympathetic and parasympathetic dominance at different phases of heat acclimation (Horowitz and Meiri 1993). Our study clearly demonstrated that heat acclimation was accompanied by vagal dominance, which was observed as early as the rest period of the heat tolerance test conducted during day 14 and remained apparent until the end of the test for the majority of the HrV indices extracted.…”
Section: Discussionmentioning
confidence: 99%
“…this heat acclimation-induced bradycardia has been attributed to increased parasympathetic activity, as recorded through heart rate variability (HrV) measurements (Horowitz and Meiri 1993;Epstein et al 2010). nevertheless, the evidence on the effects of heat acclimation on AnS function appears to be inconclusive as some authors have reported an increase in sympathetic tone following heat acclimation (Frank et al 2001), or alterations between sympathetic and parasympathetic dominance at different phases of heat acclimation (Horowitz and Meiri 1993).…”
mentioning
confidence: 99%
“…The heat-adapted phenotype is acquired most effectively when hot and humid environmental conditions and physical work (intensity, duration and frequency) interact to stress thermoregulatory and cardiovascular systems (Sawka et al, 2011); this process is known as heat acclimation (Garrett et al, 2011). Primary adaptations induced by heat acclimation include decreased core temperature (Armstrong and Maresh, 1991;Buono et al, 1998;Garrett et al, 2011) and reduced heat storage (Aoyagi et al, 1997) facilitated by increased sudomotor function (Chinevere et al, 2008;Machado-Moreira et al, given workload (Frank et al, 2001). These adaptations contribute to a decreased thermal and perceptual strain (Castle et al, 2011), ultimately facilitating increased exercise performance in hot and cool environments .…”
Section: Introductionmentioning
confidence: 99%
“…Poincare plot analysis is a quantitative visual technique, whereby the shape of the plot is categorized into functional classes 16, 11. Poincare plot analysis is a quantitative visual technique, whereby the shape of the plot is categorized into functional classes 16, 11.…”
Section: The Phase-space Plot and The Multipole Methodsmentioning
confidence: 99%